2018
DOI: 10.1111/neup.12514
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem astroblastoma with MN1 translocation

Abstract: Astroblastoma is a rare glial neoplasm that occurs mostly in the cerebral hemisphere of children, adolescents and young adults. Although astroblastic perivascular pseudorosettes are unique histopathology of this neoplasm, diagnosis is usually challenging. Recently, it was discovered that the meningioma 1 gene (MN1)‐altered pediatric central nervous system high‐grade neuroepithelial tumors are actually astroblastomas. This case report presents a rare brainstem astroblastoma, with an unusual immunoprofile: negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It mostly occurs in infants and young adults, but can be observed also in adulthood (Fu et al, 2013; Merfeld et al, 2018). On imaging studies, the tumor generally appears as a well-circumscribed mass located in the cerebral hemisphere, with heterogeneous contrast-enhancement and, occasionally, cystic areas (Shin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It mostly occurs in infants and young adults, but can be observed also in adulthood (Fu et al, 2013; Merfeld et al, 2018). On imaging studies, the tumor generally appears as a well-circumscribed mass located in the cerebral hemisphere, with heterogeneous contrast-enhancement and, occasionally, cystic areas (Shin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We excluded 36 studies based on the inclusion/exclusion criteria. We identified 65 studies, including 71 patients with astroblastomas, meeting the requirements of the systematic review (Figure 2), 1–6,10,12,16–72 ranging from 2002 to 2021. In addition, we included the unpublished reports of eight patients with astroblastomas from our hospital (Table 1), resulting in a final study cohort of 79 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Another previously reported case of focal anaplasia underwent near total resection and was administered combined chemotherapy with daily carboplatin plus weekly vincristine and radiotherapy (54 Gy/30 Fr). 8) Astroblastoma with MN1 rearrangement seems to have a longer survival clinical course than anaplastic pleomorphic xanthoastrocytoma or IDH-wild-type glioblastoma. Lheman et al 9) reported in their genomic analysis of histologically diagnosed astroblastoma that MN1-rearranged cases showed a significantly better survival than BRAF-V600E mutant astroblastomas.…”
Section: Discussionmentioning
confidence: 96%
“…3,[6][7][8][9][10] Almost all patients had lesions in the cerebrum, with one patients showing a lesion in the spinal cord and another showing a lesion in the brainstem. 7,8) As in our case, Shin et al 8) reported a patient with brainstem astroblastoma with focal anaplasia. The radiological findings of astroblastoma with MN1 translocation showed the tumors to be welldemarcated, lobular or nodular, and located superficially in the cerebral hemisphere.…”
Section: Discussionmentioning
confidence: 99%